ATRT-06. SMARCB1 LOSS DRIVEN NON-CANONICAL PRC1 ACTIVITY REGULATES DIFFERENTIATION IN ATYPICAL TERATOID RHABDOID TUMORS (ATRT). (4th December 2020) - Alimova, Irina; Danis, Etienne; Weetall, Marla; Pierce, Angela M; Wang, Dong; Serkova, Natalie; Balakrishnan, Ilango; Madhavan, Krishna; Sanford, Bridget; Michel, Cole; Foreman, Nicholas K; Baird, John; et al.
Abstract: Loss of SMARCB1 is the hallmark genetic event that characterizes ATRT. SMARCB1 is a member of the SWI/SNF chromatin remodeling complex that is responsible for determining cellular pluripotency and lineage commitment. To identify co-operating epigenetic factors, we performed an unbiased shRNA screen targeting 408 epigenetic/chromatin molecules in patient-derived ATRT cell lines and identified BMI1, a component of the Polycomb Repressive Complex 1 (PRC1), as essential for ATRT cell viability. Genetic and Chemical inhibition of BMI1 inhibited clonogenic potential and induced apoptosis in vitro . In vivo PTC 596 significantly decreased growth of intracranial orthotopic ATRT tumors as evaluated by T2 MRI imaging and significantly prolonged survival compared to control animals. Using RNA-seq and ChIP-Seq our studies show that BMI1 co-operates with SMARCB1 loss to suppress transcription of pro-differentiation pathways and promote self-renewal of tumor stem cells. We then used a doxycycline-inducible SMARCB1 expression system and performed Immunoprecipitation for BMI1, followed by and mass spectrometry analysis. In SMARCB1 deficient cells BMI1 forms a partial PRC1 complex devoid of DNA binding components. Re-expression of SMARCB1 activates two PRC1 chromatin localizing components CBX4 and CBX8. CBX4 is implicated DNA damage response, tumor angiogenesis and self-renewal. CBX8 activates lineage-specific genes during differentiation of ESC. Our data suggest that SMARCB1 deletion results in reprograming of BMI1 chromatin occupancy away from lineage specification by altering the components of the PRC1 complex. These studies identify the mechanistic basis of BMI1 co-operation with SMARCB1 loss in ATRT and establish BMI1 inhibition as a novel therapeutic approach in ATRT.